Readiness of the Education System for mobile learning - Ristić, Miroslava R.; Mandić, Danimir P. (Sociološki pregled, 2018)
Many international educational systems worldwide have recognized the potentials of mobile learning, such as efciency increase, use of digital resources, cost reduction, overcoming shortcomings of traditional teaching and achieving educational outcomes. The aim of the paper is to analyze the readiness of the Serbian education system for mobile learning using the 4C method. Key results indicate that mobile learning can be signifcantly improved by: raising the digital competencies level of teachers and professional associates; system integration of mobile learning; institutional support; promoting the mobile learning concept as well as increasing investments in sustainable progress in terms of education quality and equity.
Keywords: education system; cloud computing; mobile learning; digital competencies; teacher